Telephone Survey Calling Patterns, Productivity, Survey Responses, and Their Effect on Measuring Public Opinion. Issue 3 (August 2020) - Shino, Enrijeta; McCarty, Christopher
This study examines the effect of telephone survey dialing patterns on lab productivity and survey responses. Using an original data set of paradata from 2010 to 2017 and a machine learning technique for variable selection, we find that early and late afternoon shifts are as productive as late evening shifts for both landline and cellphone Random Digit Dialing (RDD) samples. Also, early weekdays are more productive than the weekend for the cellphone RDD samples. Most importantly, time of the interview affects survey responses; therefore, survey practitioners and scholars should be cognizant of this effect when scheduling calls.